“In Fear and Night” - The Faithful Disciple in The Burial of Jesus: Narrative Reading on John 19:38-42 - Halek Bere, Paulus (Forum, 2024)
The burial of Jesus is an important aspect for Christian community to understand the meaning of salvation story. In his narrative on the burial of Jesus, John figure out three characters (Joseph of Arimathea, Pilate and Nicodemus) at the last moment of Jesus in specific way. Pilate who was fear of Jews still has authority, as the reference for Joseph of Arimathea to ask for permission in order to take the body of Jesus. In this exegetical study and narrative reading on John 19,38-42, I use the character study to approach the text as one-unit narrative. I will find out how a narrator uses setting, plot, rhetoric, and character to persuade the reader to adopt his evaluative point of view. I will argue that the burial of Jesus was the moment for them to declare themselves publicly as the true disciple of Jesus and risk their identity as Jews. By touching the death body, they made themselves impure for Jews feast, but they draw themselves near to the one who come to bring the eternal life.